2008
DOI: 10.1007/s12325-008-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic harmonic scalpel in total thyroidectomies

Abstract: Use of the UHS in thyroid surgery results in decreased operation time, drain usage and amount of bleeding and does not increase postoperative complications. The UHS is an effective, reliable and less expensive technique for thyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 10 publications
4
44
0
3
Order By: Relevance
“…Harmonic Scalpel'ın kolay kullanımı ve manipülasyonu, diseksiyon, kesme ve koagülas-yon işlemini aynı anda yapabilmesi nedeniyle operasyon süresini kısalttığı bildirilmiş ve bununda cihazın en önemli avantajı olduğu vurgulanmıştır (6,7,(15)(16)(17) (10,18,19,22). Çalışmamızda her iki grupta da kalıcı RLS hasarı gözlenmedi.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Harmonic Scalpel'ın kolay kullanımı ve manipülasyonu, diseksiyon, kesme ve koagülas-yon işlemini aynı anda yapabilmesi nedeniyle operasyon süresini kısalttığı bildirilmiş ve bununda cihazın en önemli avantajı olduğu vurgulanmıştır (6,7,(15)(16)(17) (10,18,19,22). Çalışmamızda her iki grupta da kalıcı RLS hasarı gözlenmedi.…”
Section: Discussionunclassified
“…Tiroidektomi sonrası kalıcı hipokalsemi %0,3-3 ve geçici hipokalsemi %1,6-30 arasın-da bildirilmektedir (23)(24)(25)(26)28 Bazı yazarlar Harmonic Scalpel kullanımının drenaj miktarını değiştirmediğini belirtmişler (4,12,14). Bunun aksine yapılan birkaç çalışmada da tiroidektomide Harmonic Scalpel kullanımı postoperatif drenaj miktarını azalttığı belirtilmiştir (6,7,17,22). Bizim çalışmamızda istatistiksel olarak anlamlı olmasa da Harmonic Scalpel kullanılan hastalarda ortalama drenaj miktarının daha az olduğu gözlendi.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The main advantage of using the harmonic scalpel in thyroid surgery is the reduction in operative time. Studies showed that the use of a harmonic scalpel significantly decreased the operative time (Yildirim et al, 2008, Voutilainen et al, 2000.…”
Section: Harmonic Scalpelmentioning
confidence: 99%
“…Some studies shown that no difference (Siperstein et al, 2002) was observed between the two techniques (harmonic scalpel and conventional techniques ) regarding the amount of blood loss,others (Miccoli et al, 2006,Kilic et al, 2007, Yildirim et al, 2008 have shown that drainage volume is significantly lower in patients treatment with a harmonic scalpel compared to those treated with conventional techniques.…”
Section: Harmonic Scalpelmentioning
confidence: 99%